Adsorption of C02 and CH4 on metal-cation exchange zeolite - Nor Kamarudin, Khairul Sozana (Faculty of Chemical and Natural Resource Engineering, UTM, 2008)
The effect of polyvalent cations on adsorption capacity of zeolites has been reported in the literature, which indicated that the adsorptive capacity increases with increasing charge density of the cation. The effects of metal balancing cation in zeolite structure on gas adsorption depend primarily on the size and shape of the gas molecule, the size of the cation and its location in the channel, and its interaction with the gas molecule. Modification of zeolite using cation exchange technique was used to determine the effect of different cation on gas adsorption characteristics. In this study, sodium cations originally present in zeolites are exchanged with other metal cations. It is observed that at very low concentration of adsorbed gas, the type of cation influences the adsorption characteristics, in which divalent cations adsorb more than monovalent cations exchanged zeolite. At higher concentrations of adsorbed gas, the effect of cation is insignificant. However, different gases adsorb differently depending on the adsorbate-adsorbent interactions.